The relationship between cannabis use and IVF outcome-a cohort study - Eden Har-Gil; Ayala Heled; Marjorie Dixon; Abdul Munaf Sultan Ahamed; Yaakov Bentov (BMC, 2021)
Abstract Background The effects of cannabis use on male and female reproduction have been the focus of scientific research for decades. Although initial studies raised concerns, more recent studies were reassuring. Considering the recent legalization of recreational use of cannabis in Canada, we sought to analyze IVF outcomes among users and non-users in a single IVF center. Methods This is a retrospective cohort study from a single IVF center assessing IVF outcomes among male-female, non-donor IVF patients that are either cannabis users or non-users. We analyzed the ongoing pregnancy rate as well as oocyte yield, fertilization rate, peak serum estradiol, sperm, and embryo quality. We used the Mann-Whitney test, chi-square test, and Kruskal-Wallis tests where appropriate. Results Overall, the study included 722 patients of which 68 (9.4%) were cannabis users, most defined as light users. The results of the study show similar implantation rate (40.74% vs. 41.13%) and ongoing pregnancy rate (35.2% vs. 29.1%) between the users and non-users, respectively. No significant difference between users and non-users in any of the other analyzed outcomes could be detected. Conclusions The results may provide some reassurance for the lack of any demonstrable detrimental effects of cannabis consumption on IVF outcomes. This study was limited by its retrospective nature, self-reporting of cannabis use, and a small user sample size. A larger prospective study is needed to validate its findings.